Unilateral biportal endoscopy versus percutaneous endoscopic lumbar discectomy for lumbar disc herniation: a comparative study of clinical efficacy and radiological outcomes - Li, Dongyue; Tao, Luming; Zhang, Xinuo; Su, Qingjun; Yin, Bo (BMC surgery, 2025)
Background Currently, unilateral biportal endoscopy (UBE) and percutaneous endoscopic lumbar discectomy (PELD) are increasingly being used for the treatment of lumbar disc herniation (LDH). However, there are few studies comparing the efficacy of UBE and PELD in the treatment of LDH. The aim of this study is to compare the clinical efficacy and radiological outcomes between UBE and PELD in the treatment of LDH. Methods A retrospective analysis was conducted on 108 patients with LDH treated with spinal endoscopy in our hospital from January 2021 to July 2023. Of these, 47 patients were included in the UBE group and 61 in the PELD group. Clinical parameters, including age, gender, BMI, length of hospital stay, operative time, intraoperative fluoroscopy frequency, intraoperative blood loss, pre- and postoperative hemoglobin (HGB) reduction values, follow-up duration, and postoperative complications, were recorded for both groups. Visual analog scale (VAS) scores for back and leg pain and the Oswestry Disability Index (ODI) were evaluated preoperatively, and at 1 month, 3 months, and 12 months postoperatively. The modified MacNab criteria were used to evaluate clinical efficacy at 12 months postoperatively. For radiological evaluation, lumbar MRI was used to compare changes in the anteroposterior diameter of the intervertebral disc (APDID) and dural sac cross-sectional area (DSCA) at the operated segment preoperatively and 12 months postoperatively. Results All surgeries were successfully completed. There were no statistically significant differences between the two groups in age, gender, BMI, length of hospital stay, operative time, follow-up duration, or postoperative complications (P > 0.05). The UBE group had a higher intraoperative blood loss compared to the PELD group (P < 0.05), but there was no significant difference in hemoglobin reduction values (P > 0.05). The fluoroscopy frequency in the UBE group was significantly lower than in the PELD group (P < 0.05). VAS scores and ODI values for back and leg pain significantly decreased in both groups at 1 month, 3 months, and 12 months postoperatively compared to preoperative values (P < 0.05), with no statistically significant differences between the two groups at any time point (P > 0.05). The excellent and good rates of clinical outcomes showed no significant differences between the two groups (P > 0.05). In terms of radiological results, at 12 months postoperatively, both groups showed a significant reduction in APDID and a significant increase in DSCA compared to preoperative values (P < 0.05). When comparing the both groups, the UBE group demonstrated a greater reduction in APDID and a greater increase in DSCA compared to the PELD group (P < 0.05). Conclusion Both UBE and PELD are effective in relieving pain and improving the quality of life in patients with LDH. While UBE is associated with slightly higher intraoperative blood loss, it requires fewer intraoperative fluoroscopy instances and demonstrates superior improvements in radiological parameters compared to PELD. Keywords: Unilateral biportal endoscopy(UBE), Percutaneous endoscopic lumbar discectomy(PELD), Lumbar disc herniation(LDH), Clinical efficacy, Radiological outcomes